Desenvolvimento de banhos para eletrodeposição da liga de Ni-Mo na presença do complexo bórico-sorbitol - Vitorasso, Giovana Baron (2024)
The Ni-Mo alloy is used in the industrial environment as it is characterized as a promising ecological substitute for hard chrome coating due to its excellent properties, such as high thermal stability, resistance to corrosion and wear and high hardness. The electrodepositions of Ni and Ni-Mo alloy on 1010 steel from an acid bath with the boric-sorbitol complex and using different concentrations of Na2MoO4 were investigated. From the results obtained by potentiometric titrations, the optimal pH for the baths developed was determined. Voltammetric curves showed that increasing the concentration of Na2MoO4 in the baths resulted in a decrease in current density (j). Through voltammetric studies using different scanning and rotation speEDX, it was observed that the Ni2+ reduction process was controlled by charge transfer at the beginning, and later by mixed control; and for Ni-Mo, there is mass transport control and mixed control. Galvanostatic transients significantly indicated the presence of HER in electrodepositions with jdep = -10 and -20 mA cm-2 and absence of rotation, which decreased with the presence of rotation at w = 500 rpm. Furthermore, rotation decreased the presence of Ni(OH)2 precipitated on the surface of the deposits produced. The Ni electrodeposits were opaque and whitish, while the Ni-Mo deposits obtained without rotation were bright, non-uniform, with gray tones and/or brownish regions. Upon rotation, the Ni-Mo electrodeposits were brown or colored, possibly due to the presence of molybdenum oxides. Characterization by SEM revealed globular morphologies for the Ni electrodeposits, and smooth and with the presence of irregular crystallites dispersed for the Ni-Mo deposits, mostly. The Mo contents obtained in Ni-Mo alloys from the baths developed were high and efficient when compared to the literature, with the deposit being produced with w = 500 rpm, jdep = -3 mA cm-2, from bath 0.24 M Ni2+ / 0.020 M MoO42-, responsible for the highest content of 67.8%m of Mo. The efficiency of Ni-Mo electrodeposits produced from baths and deposition conditions varied between 2.7 and 9.3%, being significantly lower than the efficiency resulting from Ni electrodeposits, from 57.4% to 78.4%. A possible justification for this is the high presence of HER parallel to the Ni-Mo reduction process, this alloy being catalytic for this reaction. By XRD, crystalline Ni phases were observed in Ni electrodeposits, and in Ni-Mo electrodeposits, it was observed that the vast majority of electrodeposits could be characterized as a solid solution of Mo in Ni. Through the adherence test, it was found that all Ni and Ni-Mo deposits produced in the absence of rotation were classified as Gr0 by NBR 11003. In the presence of rotation, adherence depended on the parameters and deposition baths. It can be concluded that the Ni and Ni-Mo deposition baths in the presence of CBS developed in this work were efficient in producing electrodeposits with high Mo contents in the chemical composition (in the case of Ni-Mo), adherent and with the absence of cracks.